The Effect Of Corporate Social Responsibility On Company Performance With Goog Corporate Governance As A Moderating Variable - Kenneth Nathanael; Andayani, Wuryan (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on the performance of Kompas 100 Index companies for the 2021–2023 period, as measured by Return on Assets (ROA), with moderation by Good Corporate Governance (GCG), proxied by managerial ownership. The inconsistency of previous research results and the importance of CSR in business strategy form the background of this study. Panel data regression using the Random Effect model is applied to 135 observations from 45 companies over three years. The results show that CSR has no significant effect on ROA, managerial ownership has no significant effect on ROA, and GCG does not moderate the relationship between CSR and ROA. These findings indicate that CSR disclosure and managerial ownership do not significantly improve company financial performance. The limitation of this study lies in the low Adjusted R² value (4.18%). Therefore, future research should consider additional variables, such as leverage and Return on Equity (ROE), to enhance the relevance of the findings.